Cost–effectiveness of vaccinating the elderly and at-risk adults with the 23-valent pneumococcal polysaccharide vaccine or 13-valent pneumococcal conjugate vaccine in the UK. (December 2014) - Jiang, Yiling; Gauthier, Aline; Keeping, Sam; Carroll, Stuart
Abstract : Objective: The introduction of routine childhood vaccination with pneumococcal conjugate vaccines (PCVs) has led to a decrease in the overall incidence of pneumococcal disease in all ages and a change in the serotype distribution of the remaining disease. This study assessed the cost–effectiveness of vaccinating ≥65 years and at risk adults with either the 23-valent pneumococcal polysaccharide vaccine (PPV23) or the 13-valent conjugate vaccine (PCV13) in the UK, accounting for epidemiological changes. Methods: A population-based Markov model was used to track one UK-based cohort of individuals assuming PPV23, PCV13 or no vaccination until death. Results: The ICER was estimated at £8413 when PPV23 was compared to no vaccination. PPV23 dominated PCV13. Conclusion: This model suggests that vaccinating with PPV23 is cost-effective when compared to both PCV13 and no vaccination. As PPV23 covers 80–90% in the UK of all serotypes causing invasive pneumococcal diseases, it remains cost-effective despite recent reductions in invasive pneumococcal diseases incidence in adults.